2006
DOI: 10.1016/j.jtcvs.2005.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Performance of bioprostheses and mechanical prostheses assessed by composites of valve-related complications to 15 years after aortic valve replacement

Abstract: No differences were observed in valve-related reoperation and mortality in patients >60 years. Comparative evaluation gives high priority for bioprostheses in patients >60 years based on improved morbidity profile. This evaluation extends this center's recommendation for bioprostheses in aortic valve replacement to include patients >60 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 14 publications
(13 reference statements)
3
48
0
Order By: Relevance
“…17 Models were constructed by incorporating (1) variables with PՅ0.10 on log-rank testing, and (2) previously described risk factors associated with reoperation for patients undergoing AVR or MVR. 18 …”
Section: Discussionmentioning
confidence: 99%
“…17 Models were constructed by incorporating (1) variables with PՅ0.10 on log-rank testing, and (2) previously described risk factors associated with reoperation for patients undergoing AVR or MVR. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The proportional hazards assumption was verified by testing Schoenfeld residuals and built by incorporating variables with PՅ0.10 on log-rank testing; patient and operative characteristics that differed between prosthesis groups, and previously described risk factors associated with survival for patients undergoing AVR. 19 All covariates were entered into the final model simultaneously. Multivariable modeling was not performed for the outcome of reoperation given the low number of events.…”
Section: Discussionmentioning
confidence: 99%
“…10 There are several retrospective studies which showed improved survival in mechanical valves, 11,12 but more recent larger series indicate no difference in early and late mortality in both AVR and MVR. [13][14][15][16] one of the largest retrospective series was published by van Geldorp et al 17 which assessed 3934 patients who underwent AVR. After microsimulation, for a 60-year-old man, simulated life expectancy in years for biological versus mechanical prostheses were similar (11.9 years versus 12.2 years).…”
Section: Survivalmentioning
confidence: 99%
“…12,14,15 In microsimulation, simulated lifetime risk of bleeding was 12% in bioprostheses versus 41% in mechanical valve for a 60-year-old man. 17 It cannot be ignored that overall observed mortality of a bleeding event was 22%, which is much higher than published reoperation AVR mortality (5% to 6%).…”
Section: Bleeding and Anticoagulationmentioning
confidence: 99%
See 1 more Smart Citation